125k views
0 votes
PLSSS HELPPPPP!!!! Evaluate the expression. -1 - (-6 + 10) = -1 =​

PLSSS HELPPPPP!!!! Evaluate the expression. -1 - (-6 + 10) = -1 =​-example-1
User Kitlbast
by
4.3k points

2 Answers

3 votes
First you solve what is in the bracket you get 4
So -1 + 4 /4
Divide you get 1
So the answer is 0
User Lazycs
by
5.2k points
6 votes

Answer:

3

Explanation:

Given

- 1 - (- 6 + 10 ) ÷ - 1 ← evaluate parenthesis

= - 1 - (4) ÷ - 1

= - 1 - 4 ÷ - 1 ← evaluate division

= - 1 + 4

= 3

User Khaledh
by
5.4k points